2016
DOI: 10.1002/brb3.581
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal cortical thinning and aggression in mild traumatic brain injury patients

Abstract: IntroductionAlthough mild traumatic brain injury (mTBI) comprises 80% of all TBI, the morphological examination of the orbitofrontal cortex (OFC) in relation to clinical symptoms such as aggression, anxiety and depression in a strictly mTBI sample has never before been performed.ObjectivesThe primary objective of the study was to determine if mTBI patients would show morphological differences in the OFC and if the morphology of this region would relate to clinical symptoms.MethodsUsing structural images acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…An alternative interpretation of our findings could be that reduced white matter integrity in the corpus callosum results in decreased behavioral inhibition. Prior studies have documented increased aggression in patients with orbitofrontal damage (Coccaro et al, 2007 ; Epstein et al, 2016 ). Our findings indicate similar behavioral tendencies (increased aggression) associated with reduced structural integrity in the corpus callosum, which may disrupt interhemispheric signal transfer and impede cortically mediated inhibitory processes necessary for context-appropriate behavioral regulation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…An alternative interpretation of our findings could be that reduced white matter integrity in the corpus callosum results in decreased behavioral inhibition. Prior studies have documented increased aggression in patients with orbitofrontal damage (Coccaro et al, 2007 ; Epstein et al, 2016 ). Our findings indicate similar behavioral tendencies (increased aggression) associated with reduced structural integrity in the corpus callosum, which may disrupt interhemispheric signal transfer and impede cortically mediated inhibitory processes necessary for context-appropriate behavioral regulation.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have reported increased aggression following traumatic brain injury (Kim et al, 1999 ; Bailie et al, 2015 ; Epstein et al, 2016 ; Roy et al, 2017 ), yet few have restricted participant samples to chronic mTBI to investigate the presence of persistent and potentially long-lasting symptoms associated with brain injury. Consistent with a recent study by Epstein et al ( 2016 ), we found increased physical aggression, anger, and total aggression on the BPAQ following mTBI. Additionally, measures of aggressive attitude and total aggression on the PAI were elevated in those with mTBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Most studies that reported changes in regional brain volume showed changes in regions such as the frontal gyri, precuneus, temporal gyri, caudate, cingulum, and hippocampus. 6,8,15,27,28 The ITK-SNAP protocol we used is robust to discrimination of bone, fluid, and soft tissue on CT but cannot discriminate soft-tissue differences (eg, gray versus white matter) sufficiently to allow regional segmentation. Currently available regional segmentation algorithms such as FreeSurfer (http://surfer.nmr.mgh.harvard.edu) are validated for parcellation of MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who have sustained severe TBI may exhibit organic aggressive syndrome (OAS), characterized by unplanned, non-purposeful violence in response to seemingly trivial stimuli (Wortzel & Arciniegas, ]). Mild TBI, the "signature" injury of the Iraq and Afghanistan wars (Hayward, 2008), has similarly been associated with aggressive and criminal behavior (Epstein, Legarreta, Bueler, King, & McGlade, 2016). However, personality traits, substance use, co-occurring psychiatric illness, and generalized impaired impulse control are confounding factors to the determination of a causal connection (Wortzel, Brenner, & Arciniegas, 2013).…”
mentioning
confidence: 99%